(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this increasingly rapidly developing era, there are more technological advances, therefore more and more technology users, one of which is smartphones. Many new things have sprung up that make human life easier, one of the results of this smartphone revolution is the increasing number of smart applications, one of which is an amazing money-making application that is widely used by teenagers is the “Whaff Reward” application. In this application you can use it to get money with a dollar amount, just by doing the tasks you are told to do. With the Whaff Reward application, teenagers can easily earn money.